Elite in social networks: new forms of feedback in the digital age - O. V. Kryshtanovskaya (Цифровая социология, 2019)
The article presents the data of sociological research of the Russian political elite and its activity in social networks (using the example of the social network “Twitter”). The study was conducted by analyzing a database, containing information about the presence of accounts, subscriptions and the size of the audience, the content of published materials of representatives of the Russian establishment. The object of the study were the deputies of the State Duma of the Federal Assembly of the Russian Federation of the VI convocation and of the Federation Council of the Federal Assembly of the Russian Federation, senior officials of the Presidential Administration of the Russian Federation, members of the Government of the Russian Federation, heads of Subjects of Federation . The basic indicators of the analysis of online activity of elite have been revealed, it has been analyzed how their activity in social networks affects popularity and authority of the power. The analysis of the presence on Twitter of various groups of the ruling elite (representatives of both executive and legislative bodies of power and administration of the country), their activity, the content of published texts, has been made. The index of authority, reflecting popularity of each representative of establishment in circles of ruling elite has been constructed. The method has allowed us to identify not only leaders of public opinion in a network, but also to find the most influential persons in circles of the persons making the state decisions. A significant delay of the authorities in the use of new technologies to promote their policies has been revealed. The need to develop this sector of communication between the government and society in the digital age is obvious.